USP8 inhibition reshapes an inflamed tumor microenvironment that potentiates the immunotherapy - Xiong, Wenjun; Gao, Xueliang; Zhang, Tiantian; Jiang, Baishan; Hu, Ming-Ming; Bu, Xia; Gao, Yang; Zhang, Lin-Zhou; Xiao, Bo-Lin; He, Chuan; Sun, Yishuang; Li, Haiou; et al. (Nature communications, 2022)
Anti-PD-1/PD-L1 immunotherapy has achieved impressive therapeutic outcomes in patients with multiple cancer types. However, the underlined molecular mechanism(s) for moderate response rate (15–25%) or resistance to PD-1/PD-L1 blockade remains not completely understood. Here, we report that inhibiting the deubiquitinase, USP8, significantly enhances the efficacy of anti-PD-1/PD-L1 immunotherapy through reshaping an inflamed tumor microenvironment (TME). Mechanistically, USP8 inhibition increases PD-L1 protein abundance through elevating the TRAF6-mediated K63-linked ubiquitination of PD-L1 to antagonize K48-linked ubiquitination and degradation of PD-L1. In addition, USP8 inhibition also triggers innate immune response and MHC-I expression largely through activating the NF-κB signaling. Based on these mechanisms, USP8 inhibitor combination with PD-1/PD-L1 blockade significantly activates the infiltrated CD8 + T cells to suppress tumor growth and improves the survival benefit in several murine tumor models. Thus, our study reveals a potential combined therapeutic strategy to utilize a USP8 inhibitor and PD-1/PD-L1 blockade for enhancing anti-tumor efficacy. The regulatory mechanisms of PD-L1 posttranslational modifications are not completely understood. Here the authors show that USP8 negatively regulates PD-L1 protein abundance by removing the K63-linked ubiquitination of PD-L1; while USP8 inhibition increases MHC-I expression and triggers anti-tumour immune responses through activating NF-κB signalling.